Comparison Of Bacillus anthracis Prepared Used Antigens As ‎Diagnostic kit Of Anthrax In Laboratoy Animals.‎ - Al- Jebouri A.J. ‎; Al- Khatib G.M.‎ (The Iraqi Journal of Veterinary Medicine)
This study was concerned on the preparation of several antigens on different